Pro-poor Growth: Explaining the Cross-Country Variation in the Growth Elasticity of Poverty - Chhibber, Ajay (2012)
The aim of this paper is to analyse the cross-country variation in the growth elasticity of poverty across a sample of developing countries during the period from 1990 to 2000. In order to identify variables that may explain the cross-country variation in the growth elasticity of poverty, the paper sets up a theoretical framework. Subsequently, the explanatory power of these variables is tested empirically by panel data econometric analysis. For a sample of 52 low and middle income countries, it is found that the level of initial income inequality, credit available to the private sector, literacy, the extent of business regulations and trade openness are important determinants of the growth elasticity of poverty. Countries that reduce regulatory burdens, improve literacy, increase access to finance, undertake land reforms (asset redistribution), and provide safety nets while liberalizing trade can create more growth and ensure that it is pro-poor. The paper identifies variables (at a cross-country level) that may guide the conscious policies which create pro-poor growth.